Insulation coordination study of 275kV AIS substation in Malaysia - Mokhlis, Hazlie; Bakar, Ab Halim Abu; Illias, Hazlee Azil; Shafie, Mohd Fakrolrazi (2012)
Over voltages are phenomena which occur in power system networks, either externally or internally. The selection of certain level of over voltages which are based on equipment strength for operation is known as insulation coordination. A study has been carried out to investigate over voltages due to lightning, which is affecting an air insulated substation (AIS). The objective of this study is to determine whether the withstand capability or the Basic Insulation Level (BIL) is the cause of fault occurring in a substation